Mycobacterium ulcerans Triggers T-cell immunity followed by local and regional but not systemic immunosuppression - Fraga, Alexandra G. (2011)
Buruli ulcer (BU) is a neglected infectious disease caused by Mycobacterium ulcerans, characterized by necrotic cutaneous lesions induced by the exotoxin mycolactone. Despite evidence of Th1-mediated protective immunity, M. ulcerans infection has been associated with systemic immunosuppression. We show that early during mouse infection with either mycolactone-positive or negative strains, pathogen-specific IFN-γ-producing T cells developed in the draining lymph node (DLN). CD4+ cells migrated to infection foci but progressive infection with virulent M. ulcerans led to the local depletion of recruited cells. Moreover, dissemination of virulent M. ulcerans to the DLN was accompanied by extensive DLN apoptotic cytopathology leading to depletion of CD4+ 31 T cells and abrogation of IFN-γ expression. Advanced footpad infection with virulent M. ulcerans did not induce increased susceptibility to systemic co-infection by Listeria monocytogenes. These results show that infection with M. ulcerans efficiently triggers a mycobacteria-specific T cell response in the DLN and that progression of infection with highly virulent M. ulcerans leads to a local and regional suppression of that immune response, but without induction of systemic immunosuppression. These results suggest that prophylactic/therapeutic interventions to prevent dissemination of M. ulcerans to DLN during the early phase of infection would contribute for the maintenance of protective immunity and disease control.